Features of use depoforez of hydrooxigen copper-calcium in chronic apical periodontitis (Эндодонтия Today)
Opportunity and advantages of use depoforez of hydrooxigen copper-calcium («Kupral») in chronic apical periodontitis are considered in this issue. Special chemical properties of suspension provide high and long bacteriological activity of medicine in inflammatory center. The application technique of depoforez of hydrooxigen copper-calcium is described in the issue, efficiency of the method is confirmed with clinical and radiological examples. Alternative way of treatment of chronic apical periodontitis by means of depoforez of hydrooxigen copper-calcium allows stop the expansion of inflammatory center, accelerate recovery of bone tissue and keep doubtful teeth in the mouth.